Causal and non-causal explanations in theology: the case of Aquinas's primary -secondary causation distinction - Silva, Ignacio Alberto (Religious studies, 2025)
The basic question of this article is whether Thomas Aquinas's doctrine of divine providence through his understanding of primary and secondary causation can be understood as a theological causal or non-causal explanation. To answer this question, I will consider some contemporary discussions about the nature of causal and non-causal explanations in philosophy of science and metaphysics, in order to integrate them into a theological discourse that appeals to the classical distinction between God as first cause and creatures as secondary causes to explain God's presence and providence in the created universe. My main argument will hold that, even if there are some philosophical models of explanation that seem to allow one to suggest that, at least partially, this doctrine could be seen as a non-causal theological explanation, there are other models that offer seemingly stronger reasons to see this doctrine in full as a causal theological explanation.